2003
DOI: 10.1002/chem.200304727
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Spectroscopic and Theoretical Study of a Series of Conformationally Restricted Hexapeptides Carrying a Rigid Binaphthyl–Nitroxide Donor–Acceptor Pair

Abstract: The structural features of a series of linear hexapeptides of general formula Boc-B-A(r)-T-A(m)-OtBu, where A is L-Ala or Aib (alpha-aminoisobutyric acid), B is (R)-Bin, a binaphthyl-based C(alpha,alpha)-disubstituted Gly residue, T is Toac, a nitroxide spin-labeled C(alpha,alpha)-disubstituted Gly, and r+m=4, were investigated in methanol solution by fluorescence, transient absorption, IR and CD spectroscopic studies, and by molecular mechanics calculations. These peptides are denoted as B-T/r-m, to emphasize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
2

Relationship

6
3

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 57 publications
1
11
0
Order By: Relevance
“…where τ i is the ith decay time observed and α i is the ith preexponential factor that represents the relative contribution of the decay to the emission intensity [35][36][37] From quantum yield values and decay data it is possible to obtain the radiative (k r ) and non-radiative (k nr ) constants for 1PN. 38 The solvents used, i.e., acetonitrile (ACN) and cyclohexane (CHEX) span a wide polarity range in terms of both different orientation polarizability ( f p ) and empirical "py scale."…”
Section: Materials and Experimental Methodsmentioning
confidence: 99%
“…where τ i is the ith decay time observed and α i is the ith preexponential factor that represents the relative contribution of the decay to the emission intensity [35][36][37] From quantum yield values and decay data it is possible to obtain the radiative (k r ) and non-radiative (k nr ) constants for 1PN. 38 The solvents used, i.e., acetonitrile (ACN) and cyclohexane (CHEX) span a wide polarity range in terms of both different orientation polarizability ( f p ) and empirical "py scale."…”
Section: Materials and Experimental Methodsmentioning
confidence: 99%
“…In cases where the center-to-center TOAC–fluorophore distance was more than 9 Å, the quenching mechanism was described as a Förster energy transfer (dipole–dipole interaction) from the excited fluorophore to TOAC, provided the mutual orientation of the fluorophore and TOAC was taken into account (Pispisa et al 1998; Toniolo et al 1998, 1999; Pispisa et al 2000a, b, 2002, 2003a, b). Time-resolved EPR with pulsed laser excitation experiments showed that the intramolecular quenching by TOAC of a fluorophore in the triplet excited state occurs by enhanced intersystem crossing to the ground state via an electron-exchange process (Corvaja et al 2000a, b).…”
Section: Synthetic Peptidesmentioning
confidence: 99%
“…[14,15] It has been shown that for Fmoc···TOAC centre-tocentre distances longer than 4-5 , the Fçrster dipole-dipole interaction model [27] adequately describes the excited state interaction between the aromatic molecule and the nitroxyl radical quencher. [28] At shorter distances, the overlap of the electronic distributions gives rise to ultrafast relaxation mechanisms that completely deplete the fluorescence emission. Time-resolved fluorescence experiments have been performed to study the peptide conformational and dynamic properties in the nanosecond time region.…”
Section: Fluorescence Experimentsmentioning
confidence: 99%
“…In a series of papers we have shown that time-resolved FRET experiments and theoretical conformational analysis can be jointly applied to determine the conformational properties of sterically constrained oligopeptides in solution. [28] According to the Fçrster model, [27] the energy transfer quenching efficiency is given by Equation (3), where R m and k 2 m are the D···A centre-to-centre distance and the D···A orientation factor in the mth conformer, respectively.…”
Section: Conformational Analysis By Molecular Mechanics a C H T U N Gmentioning
confidence: 99%